Colonial Legacy and its Impact : Analyzing Historical Tactics, Institutional Structures, and Enduring Division In Pakistan and India - Sahito, Muhammad Shahban; Noonari, Majid Ali; Iqbal, Iqra M. (Annals of Human and Social Sciences, 2022)
This research paper discusses Colonial Legacy and Its Impact. It further elaborates Strategies of Colonial Rule, exploring the divide-and-rule tactics employed by the colonial powers and their lasting impact on societal divisions. In addition, it explains the legacy of institutional structures, discussing how colonial governance shaped institutions and political classes, perpetuating societal disparities, post-independence, and continuing social divisions. The study briefly summarizes existing work on identity politics in terms of the us-other concept, as well as how colonial rule formed institutions and political classes, maintaining societal inequities, post-independence, and ongoing social divisions. Colonial ideology have also had a significant impact on the political landscapes of Pakistan and India. The results indicate that, it analyses the enduring effects of colonial ideologies on societal and political landscapes in Pakistan and India. It defines struggles for unity and progress. It defines struggles for unity and progress. In the end, it highlights the challenges faced in overcoming deep-rooted divisions and fostering a cohesive national identity. Apart from that, it highlights the complexities faced by societies in overcoming colonial legacies.